EXTH-39. EFFICACY OF THE ANTIBODY-DRUG CONJUGATE ABT-414 IN BRAIN TUMOR MODELS - Muldoon, Leslie (Neuro Oncol, 2017)
Brain tumor treatment is limited by a lack of effective therapies and inadequate drug delivery across the blood-brain barrier (BBB). The antibody-drug conjugate (ADC) ABT-414 (AbbVie Pharmaceuticals) couples the toxin monomethyl auristatin F to a humanized monoclonal antibody targeting overexpressed and mutant epidermal growth factor receptor (EGFR). ABT-414 inhibits tumor growth in multiple preclinical subcutaneous tumor models, but its efficacy in brain tumors may be reduced by inadequate delivery of the ADC across the BBB after intravenous administration. We have shown that intra-arterial infusion of hypertonic mannitol transiently disrupts the BBB to safely increase delivery of chemotherapy, antibodies and nanoparticles to the brain. We hypothesized that BBB disruption (BBBD) would improve ABT-414 efficacy in rat models of human brain tumors. Using intracerebral xenografts of U87MG human glioma cells expressing EGFRvIII (U87-EGFRv3), we found that ABT-414 is highly effective when delivered with BBBD as a single dose at concentrations as low as 1 mg/kg. One week after treatment, the tumor volume of treated animals was 0.47 ± 0.27mm(3) (n=3) relative to controls 31.1 ± 8.3mm(3) (n=10) (P<0.0001). Immunohistochemistry demonstrated apparent residual tumor consisting of a glial scar along the inoculation track with ~1–3 tumor cells present per section. Using ferumoxytol-enhanced magnetic resonance imaging to detect treatment-induced inflammatory responses, we observed strong signal dropout at tumor sites that co-localized with ferumoxytol uptake in activated macrophage/microglia within and around the residual lesion. Finally, we found that ABT-414 was partially effective in an intracerebral xenograft model using wildtype EGFR human non-small cell lung cancer cells. We conclude that BBBD delivery of ABT-414 is safe in rat brain and the immunoconjugate is highly effective in the treatment of rat brain tumor models.